Directional Solidification of Sn-Ag-Cu Alloys - Fornaro, Osvaldo (2015)
The alloys of Sn-Ag-Cu family (SAC) are candidates for lead-free replacement of Sn-Pb eutectic used in welding processes of electronic devices. These alloys, with eventual adding of Zn, In and Bi highly improves the morphological stability and the corrosion resistance. Close to the eutectic ternary composition, the solidification occurs with three distinct phases: Sn-rich dendritic primary phase, Ag3Sn and Cu6Sn5 intermetallic phases, which have limited solubility in the Sn phase, in such a way that some authors consider these alloys as compounds of Sn with the mentioned intermetallic phases. In this aspect, the directional solidification is a suitable tool to study the solidification under strictly controlled conditions. In this work, samples of Sn-Ag-Cu composition were grown to analyze the mechanisms involved in the solidification of these alloys. The typical microstructure agrees the above description, with a spacing that depends mainly on the advance interface velocity of the growth.